2020
DOI: 10.15358/2511-8676-2020-4-187
|View full text |Cite
|
Sign up to set email alerts
|

Digital Disruption in Retailing and Beyond

Abstract: The increased disruption of business models through digital technologies creates opportunities and challenges for retail businesses and their network partners. Digital transformation – the process of digitalization of previously analogue operations, procedures, organizational tasks, and managerial processes in order to drive value for customers, employees and other stakeholders – is the order of the day. With that in mind, this article provides a purposeful overview of research in the field of digital transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 97 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…This framework can be used for developing HAT to support job performance while addressing the impact on the employees' well-being. Previous studies providing R&D agenda for HAT generally focus on specific topics or tools such as performance of military [64], brain-computer interface [65], and retail business [66]. This study describes comprehensive employee well-being from the viewpoints of technology demand and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…This framework can be used for developing HAT to support job performance while addressing the impact on the employees' well-being. Previous studies providing R&D agenda for HAT generally focus on specific topics or tools such as performance of military [64], brain-computer interface [65], and retail business [66]. This study describes comprehensive employee well-being from the viewpoints of technology demand and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The paper by (Evanschitzky et al, 2020) offers a review of digital transformation research with an emphasis on retailing and consumer-facing digital technology roles, such as customer journey management, on the one hand, evaluating the effect of sensory marketing and the use of service robots, on the other hand, and their strategic implications for business models such as sterilization.…”
Section: Impact Of Technology and Digital Innovationsmentioning
confidence: 99%
“…The best-practice examples demonstrate how to give their customers a high shopping experience; certain retailers have continued to benefit from the specific qualities of physical and digital touchpoints. While these two studies offer some answers to the above research questions, further study is needed to better understand the diverse consumer journeys of today and to deal effectively with the emerging digital touchpoints that will emerge in the future (Evanschitzky et al, 2020).…”
Section: Impact Of Technology and Digital Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the acceptance of information and communication technologies creates disruption in purchase behavior, the building and sustaining of customer loyalty remains an ongoing challenge for retailers (e.g., Evanschitzky et al, 2020). Loyalty has been shown to affect important downstream outcomes (e.g., Evanschitzky et al, 2012;Love et al, 2016;Mende et al, 2015), and it has been suggested that finding new customers is costlier than retaining existing customers (e.g., Davis-Sramek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%